Effect of lipid surface charges on the purple-to-blue transition of bacteriorhodopsin. - Szundi, I (1987)
Purple membrane (lambda max = 568 nm) can be converted to blue membrane (lambda max = 605 nm) by either acid titration or deionization. Partially delipidated purple membrane, containing only 25% of the initial lipid phosphorus, could be converted to a blue form by acid titration but not by deionization. This reversible transition of delipidated membrane did not require the presence of other cations, and the pK of the color change that in native membrane under similar conditions is between 3.0 and 4.0 was shifted to 1.4. We conclude that the purple-to-blue transition is controlled by proton concentration only and that, in native membranes, the cations act only by raising the low surface pH generated by the acidic groups of the lipids. The observation that extraction of lipids from deionized native membrane converts its color from blue to purple further confirms this conclusion. The two states of the membrane probably reflect two preferred conformations of bacteriorhodopsin, which are controlled by protonation changes at the surface of the membrane and differ slightly in the spatial distribution of charges around the chromophore.